Treatment of scars with botulinum toxin: level of scientific evidence (Anales de la Real Academia de Medicina y Cirugía de Valladolid, 2023)
:  Keloid scars represent the highest degree of anti-aestheticism of the spectrum of scar hypertrophy and constitute a real clinical challenge. Numerous therapeutic strategies have been described aimed at this type of scars, such as surgery, laser, radiofrequency, and infiltration, among others. However, the ideal therapeutic approach has not been achieved so far.Recently, the use of Botulinum Toxin type A (BoNT-A) has been published as part of the treatment of keloid scars with controversial results. A review of the scientific evidence of studies comparing the use of BoNT-A with the use of intralesional corticosteroids was carried out, as well as its mechanism of action and side effects.The results of systematic reviews for the prevention and/or treatment of hypertrophic or keloid scarring with BoNT-A do not show consistent scientific evidence. Furthermore, it is difficult to obtain conclusive data due to the small size of the cohorts, the difficulty in extrapolating the results of animal experimentation to the general population and the heterogeneity existing in the different studies.Scientific evidence considers that it is possible to carry out an "off- label" use of BoNT-A since it is effective and safe as a treatment to prevent or improve unsightly scars. On the other hand, despite the fact that corticosteroids could be superior to BoNT-A in some aspects, it seems that the side effects associated with its use could be avoided with the use of botulinum toxin.
Keywords: Botulinum toxins Type A, cicatrix, collagen, hypertrophic cicatrix, fibroblasts, keloid, triamcinolone acetonide.